Alkaline electrolytic water hydrogen production composite diaphragm and preparation method thereof
By adopting a new composite diaphragm preparation method in alkaline electrolytic hydrogen-making diaphragm, the existing diaphragm has solved the problems of powder loss, poor airtightness and poor bending resistance in high-pressure environments, achieving uniform dispersion of inorganic particles and channel density, improving the airtightness and hydrophilicity of the diaphragm, and is suitable for the application of domestic high-voltage electrolytic cells.
Patent Information
- Application Number
- CN202510079035.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-05-09
AI Technical Summary
When used in domestic high-voltage electrolytic cells, existing alkaline hydrolyzing hydrogen diaphragms have problems such as powder loss, poor airtightness, poor bending resistance and uneven texture, which affects its application in high-voltage environments.
A new composite separator preparation method is adopted to form a cast film liquid by uniformly mixing the inorganic powder, resin and solvent, and then coated on both sides of the base film with two phase conversion and vacuum drying to fix the inorganic particles and solvent to form a composite separator with dense pores and high hydrophilicity.
It realizes uniform dispersion of inorganic particles in the diaphragm and denseness of the pores, improves the air-tightness and hydrophilicity of the diaphragm, solves the problems of powder loss and poor bending resistance, and is suitable for domestic high-voltage electrolytic cells.
Smart Images

Figure CN119956423A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water electrolysis hydrogen production materials, and in particular to an ultra-dense pore alkaline water electrolysis hydrogen production composite diaphragm and a preparation method thereof. Background Art
[0002] In recent years, new energy industries such as photovoltaics, wind power and lithium batteries have developed rapidly. However, since photovoltaics and wind power are easily affected by climate and fluctuate violently, which has a great impact on the power grid, most of the electricity has been abandoned. The rational use and consumption of new energy has become an important issue restricting their development.
[0003] The development of new energy storage technologies such as hydrogen energy, lithium batteries, sodium batteries and flow batteries is the key to promoting the development of new energy. Hydrogen energy is not only an energy source, but also an important chemical raw material. Hydrogen is generally divided into gray hydrogen, blue hydrogen and green hydrogen according to the production method. Among them, hydrogen produced by electrolyzing water using new energy is called green hydrogen. Currently, the proportion of green hydrogen does not exceed 1%. Using green hydrogen to replace gray hydrogen and blue hydrogen is an inevitable trend to rationally utilize new energy and reduce carbon emissions.
[0004] Commercial water electrolysis hydrogen production is mainly divided into alkaline water electrolysis hydrogen production (ALK) and proton exchange membrane water electrolysis hydrogen production (PEM). ALK technology is the mainstream water electrolysis hydrogen production technology in China, but its operation requires a stable power supply, while photovoltaic and wind power generation fluctuates greatly and is poorly compatible with ALK technology.
[0005] In the early stage of ALK electrolyzer startup, a small portion of the hydrogen produced at the cathode will penetrate through the diaphragm to the oxygen side of the anode, causing the hydrogen content in the oxygen to exceed the standard and posing a risk of explosion. The diaphragm is the key material for the electrolyzer. Improving the airtightness and hydrophilicity of the diaphragm can effectively prevent hydrogen from penetrating into the oxygen side, improve the safety of the electrolyzer, shorten the cold start time, and improve compatibility with wind and solar power.
[0006] The alkaline water electrolysis hydrogen production diaphragm currently used is a polyphenylene sulfide woven diaphragm, which has high mechanical strength, but because it is a woven diaphragm, the gap is >1um, and polyphenylene sulfide has poor hydrophilicity, so its surface resistance is high and the energy consumption is poor. Chinese invention patent CN115997046A discloses a composite diaphragm, which uses a polyphenylene sulfide woven mesh as a substrate, is coated with polysulfone and zirconium oxide, and then obtained through a two-step phase conversion step. Compared with the traditional polyphenylene sulfide woven diaphragm, the film has the advantages of good air tightness and low energy consumption.
[0007] However, the above-mentioned composite diaphragm and similar products are mainly used in square electrolytic cells in Europe. There is a big difference between domestic electrolytic cell technology and square electrolytic cells: the operating pressure of square electrolytic cells is low, only about 0.5MPa, and domestic electrolytic cells are mostly circular electrolytic cells with an operating pressure of >1.6MPa. The composite diaphragm showed serious powder loss during the test of domestic high-pressure electrolytic cells.
[0008] How to develop a composite diaphragm suitable for domestic high-voltage electrolyzers is a hot topic in the industry. For example, PCT patent WO2024 / 140892A1 introduces a method for preparing a high-temperature resistant composite diaphragm, using ice water to reduce the LIPS phase transition temperature to obtain a composite diaphragm with denser pores. However, after the above-mentioned diaphragm comes into contact with water, the air inside it will undergo a phase transition process with the water and be exchanged out. During the exchange of the solvent from the inside of the diaphragm to the water, the zirconium oxide inside the diaphragm will also flow, thereby affecting the uniformity of the zirconium oxide inside the diaphragm and causing adhesion problems between the diaphragm and the resin. In addition, poor bending resistance, poor air tightness, and uneven texture are also problems with current diaphragms. Summary of the invention
[0009] In view of the shortcomings of the prior art, the present invention discloses an alkaline water electrolysis hydrogen production composite diaphragm and a preparation method thereof. Compared with the traditional method, the inorganic particles in the composite diaphragm prepared by the method of the present invention are evenly dispersed inside, and the pores are dense. Compared with commercial diaphragms, it has strong hydrophilicity and high air tightness.
[0010] In a first aspect, the present invention provides a method for preparing a composite diaphragm for producing hydrogen by alkaline water electrolysis, comprising the following steps:
[0011] The inorganic powder, resin and solvent are mixed evenly to obtain a casting solution; the casting solution is coated on both sides of the base film;
[0012] The coated membrane is subjected to a phase inversion;
[0013] Performing a second phase transformation on the membrane that has undergone a first phase transformation;
[0014] The diaphragm that has undergone the secondary phase conversion is dried to obtain the alkaline water electrolysis hydrogen production composite diaphragm.
[0015] Phase inversion refers to forming a polymer-rich phase and a polymer-poor phase, and then separating the polymer-rich phase and the polymer-poor phase, wherein the polymer-rich phase is used for curing to form a film.
[0016] In a preferred embodiment, the particle size of the inorganic powder is D50≤5μm, preferably D50≤4μm, preferably D50≤3μm, preferably D50≤2μm.
[0017] In a preferred embodiment, the maximum particle size of the inorganic powder is no more than 10 μm, preferably no more than 9 μm, and preferably no more than 8 μm.
[0018] In a preferred embodiment, the amount of the inorganic powder is 30-50 parts by weight, preferably 35-45 parts by weight, more preferably 35-40 parts by weight, such as 36 parts by weight, 37 parts by weight, 38 parts by weight, or 39 parts by weight.
[0019] In a preferred embodiment, the amount of the resin is 8-25 parts by weight, preferably 10-20 parts by weight, such as 11 parts by weight, 12 parts by weight, 14 parts by weight, 15 parts by weight, 17 parts by weight, and 19 parts by weight.
[0020] In a preferred embodiment, the amount of the solvent is 25-50 parts by weight, preferably 30-45 parts by weight, preferably 30-40 parts by weight, such as 31 parts by weight, 33 parts by weight, 35 parts by weight, 36 parts by weight, 38 parts by weight, and 39 parts by weight.
[0021] Based on the above technical solution, in a further preferred example of the present invention, optionally: a plasticizer and / or a poor solvent is also added during the preparation of the casting solution.
[0022] In a preferred embodiment, the amount of the plasticizer is 1-5 parts by weight, preferably 1.5-4.5 parts by weight, such as 2 parts by weight, 3 parts by weight, or 4 parts by weight.
[0023] In a preferred embodiment, the amount of the poor solvent is 1-5 parts by weight, preferably 1.5-4.5 parts by weight, such as 2 parts by weight, 3 parts by weight, or 4 parts by weight.
[0024] Further optionally, the inorganic powder can be selected from 1) oxides of silicon or boron, 2) one or more of metal oxides, hydroxides, chlorides, sulfates, nitrates, and carbonates, and the metal can be one or more of zirconium, titanium, barium, magnesium, calcium, zinc, copper, silver, aluminum, and cobalt. For example, the inorganic powder can be one or a combination of two or more of zirconium oxide, zirconium hydroxide, barium sulfate, or magnesium oxide, and is preferably zirconium oxide.
[0025] Further optionally, the resin may be one or a combination of two or more selected from polysulfone, polyethersulfone, polyphenylsulfone, polyimide or sulfonated polyphenylene sulfide; preferably polysulfone.
[0026] Further optionally, the solvent is a non-aqueous solvent or a solvent that does not contain water, and can be selected from one or a combination of two or more of NMP (N-methylpyrrolidone), NEP (N-ethylpyrrolidone), NBP (N-butylpyrrolidone) or DMAC (dimethylacetamide), and is preferably NMP.
[0027] Further optionally, the poor solvent can be an alcohol, especially a C1-C10 alcohol, preferably a fatty alcohol, and can be a monohydric alcohol, a dihydric alcohol, a trihydric alcohol or more, for example, it can be selected from methanol, ethanol, ethylene glycol, propanol, glycerol, n-butanol, isopropanol, one or a combination of two or more, and preferably ethanol or glycerol.
[0028] Further optionally, the plasticizer can be one or a combination of two or more selected from dimethyl phthalate, diethyl phthalate or dibutyl phthalate, and is preferably dimethyl phthalate.
[0029] Based on the above technical solution, in a further preferred example of the present invention, optionally: the preparation temperature of the casting solution is 60-100°C, preferably 60-90°C, more preferably 60-80°C, and more preferably 65-75°C.
[0030] Based on the above technical solution, in a further preferred example of the present invention, optionally: the temperature of the base film before coating is maintained (such as can be achieved by preheating) at 60-85°C, preferably 70-80°C, more preferably 75-80°C.
[0031] Based on the above technical solution, in a further preferred example of the present invention, optionally: the coating thickness of the casting liquid on each side of the base film is independently 100-350μm, preferably 150-300μm, more preferably 300-300μm, more preferably 200-250μm.
[0032] Based on the above technical solution, in a further preferred example of the present invention, optionally: the primary phase conversion can be carried out in air, preferably, the temperature of the primary phase conversion process is 10-35°C, preferably 25-35°C, and more preferably 25-30°C.
[0033] Based on the above technical solution, in a further preferred example of the present invention, optionally: during the primary phase conversion process, the relative humidity is 50-90% RH, preferably 60-85% RH, and more preferably 70-80% RH.
[0034] Based on the above technical solution, in a further preferred example of the present invention, optionally: the residence time of the primary phase inversion process is 10-300s, preferably 30-200s, more preferably 60-120s, and more preferably 90-100s.
[0035] Based on the above technical solution, in a further preferred example of the present invention, optionally: the secondary phase inversion process, the temperature is -30°C to -100°C, preferably -50°C to -90°C, more preferably -60°C to -80°C.
[0036] Based on the above technical solution, in a further preferred example of the present invention, optionally: the residence time of the secondary phase inversion process is 1-15 min, preferably 2-15 min, and more preferably 5-10 min.
[0037] Based on the above technical solution, in a further preferred example of the present invention, optionally: the drying of the diaphragm can be a two-step drying, the first step is vacuum drying at a first temperature, and the second step is vacuum drying at a second temperature, and the second temperature is higher than the first temperature.
[0038] Preferably, the first temperature is 30-60°C, preferably 35-55°C, more preferably 40-50°C.
[0039] Preferably, the second temperature is 70-100°C, preferably 80-95°C, more preferably 85-90°C.
[0040] Preferably, the drying time of the first step is 0.5-5 h, more preferably 1-4 h, more preferably 2-3 h.
[0041] Preferably, the drying time in the second step is 0.5-5 h, more preferably 1-4 h, more preferably 2-3 h.
[0042] Preferably, the vacuum is a vacuum degree <10 4 Pa, preferably ≤5 kPa, more preferably ≤1 kPa.
[0043] The second aspect of the present invention also provides an alkaline water electrolysis hydrogen production composite diaphragm, which is composed of a base membrane and a casting liquid coating on both sides thereof.
[0044] Preferably, the alkaline water electrolysis hydrogen production composite membrane is prepared by the method described in the first aspect.
[0045] Preferably, the porosity of the casting liquid coating is 40-80%, preferably 50-70%, and more preferably 55-65%.
[0046] Preferably, the total thickness of the alkaline water electrolysis hydrogen production composite diaphragm is 200-500 μm, preferably 250-450 μm, and more preferably 300-400 μm.
[0047] Preferably, the surface resistance of the alkaline water electrolysis hydrogen production composite diaphragm is ≤0.5Ω / cm 2 , preferably ≤0.3Ω / cm 2 , more preferably ≤0.2Ω / cm 2 .
[0048] Preferably, the bubble point pressure of the alkaline water electrolysis hydrogen production composite membrane is ≥1 bar, preferably ≥1.5 bar, and more preferably ≥2 bar.
[0049] Compared with the prior art, the present invention improves the phase transformation LIPS process of the composite diaphragm, uses freezing and vacuum drying methods to replace the traditional LIPS process, and after the coated diaphragm undergoes the air vapor phase transformation process, liquid nitrogen is used as a cooling medium to freeze-dry the diaphragm, fix the solvent and inorganic particles inside the diaphragm, and do not destroy the uniformity of the inorganic particles and the solvent inside the diaphragm, and then sublimate the frozen solvent by vacuum drying. Compared with the traditional method, the inorganic particles in the composite diaphragm prepared by this method are evenly dispersed inside, and the pores are dense. Compared with commercial diaphragms, it has strong hydrophilicity and high air tightness. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention.
[0051] In the figure:
[0052] Figure 1 These are SEM photos of the diaphragm surface, where A is sample 1# and B is reference sample 1#.
[0053] Figure 2 These are SEM photos of the diaphragm surface, where A is sample 2# and B is sample 3#.
[0054] Figure 3 These are SEM photos of the diaphragm surface, where A is sample 4# and B is sample 5#.
[0055] Figure 4 The experimental results of the diaphragm bending resistance test, where A is sample 1# and B is reference sample 1#. DETAILED DESCRIPTION
[0056] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below, and preferred embodiments of the present invention are given. However, it should be understood that these embodiments are only used for more detailed description, and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the scope of protection of the present invention. Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by technicians in the field to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0057] "Range" disclosed herein is in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges that can be defined in this way are inclusive and combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, a range of 60-120 and 80-110 is listed for a particular parameter, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.
[0058] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in this document, and "0-5" is just an abbreviation of these numerical combinations.
[0059] If not specifically stated, the term "two" used in this specification means "at least two".
[0060] If not otherwise specified, the term "parts by weight" used in this specification refers to the weight ratio of each component.
[0061] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.
[0062] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0063] In the present invention, unless otherwise specified, all steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0064] In the present invention, unless otherwise specified, the term "including" mentioned herein may be open-ended or closed-ended. For example, the term "including" may mean that other elements not listed may also be included, or may only include the listed elements.
[0065] All raw materials used in the present invention can be purchased or prepared by methods known in the art.
[0066] The phase inversion used in the present invention is as follows: a polymer-rich phase and a polymer-poor phase must be formed during the phase inversion film-making process. The polymer-rich phase and the polymer-poor phase are separated under a specific environment, and the polymer-rich phase is solidified into a film. According to the different phase separation process methods, phase inversion is divided into thermal induced precipitation phase separation method, solvent evaporation precipitation phase separation method, gas phase precipitation phase separation method and immersion precipitation phase separation method (the same below). Among them, in the immersion precipitation phase conversion film-making process, the polymer solution is first placed on a specific mold by coating or casting, and then the mold is placed in a non-solvent. In the process of mutual exchange of the solvent and non-solvent of the polymer solution, a polymer-rich phase is gradually formed, and finally the polymer-rich phase is solidified into a film. The applicant has found that during the phase inversion operation, membrane materials with different structures and properties can be obtained by controlling the influencing factors at different stages such as polymer concentration, pre-evaporation time, non-solvent (also known as coagulation bath) temperature, etc.
[0067] Comparative Example 1:
[0068] (1) Coating solution preparation: zirconium oxide particles, polysulfone, and NMP were mixed together in a mass ratio of 30:10:30, and fully mixed at 60°C until they were completely dissolved and uniform. The mixed homogeneous solution was then vacuum degassed to obtain a casting solution.
[0069] (2) Coating: Heat the base film to 60°C, and use a comma scraper to evenly coat the casting liquid on both sides of the base film. The coating thickness on each side is controlled to be 100 μm.
[0070] (3) Phase inversion step 1: Place the coated membrane in an air medium at a temperature of 10° C. and a relative humidity of 50% RH for 10 seconds.
[0071] (4) Phase inversion step 2: Place the membrane in a 50°C water bath for 10 minutes.
[0072] (5) Diaphragm molding: The diaphragm was placed in an oven and dried at 50°C for 8 h. The obtained diaphragm sample was marked as reference sample 1#.
[0073] Embodiment 1:
[0074] (1) Coating solution preparation: zirconium oxide particles, polysulfone, and NMP were mixed together in a mass ratio of 30:10:30, and fully mixed at 60°C until they were completely dissolved and uniform. The mixed homogeneous solution was then vacuum degassed to obtain a casting solution.
[0075] (2) Coating: Heat the base film to 60°C, and use a comma scraper to evenly coat the casting liquid on both sides of the base film. The coating thickness on each side is controlled to be 100 μm.
[0076] (3) Phase inversion step 1: Place the coated membrane in an air medium at a temperature of 10° C. and a relative humidity of 50% RH for 10 seconds.
[0077] (4) Phase inversion step 2: Place the membrane in a -30°C liquid nitrogen environment for 10 minutes.
[0078] (5) Diaphragm molding: Place the diaphragm in a vacuum drying oven (vacuum degree <10 4 Pa), first dried at 30°C for 4 h, and then dried at 80°C for 4 h. The resulting diaphragm sample was marked as sample 1#.
[0079] like Figure 1 As shown, after freeze drying with liquid nitrogen, the solvent and inorganic particles are fixed inside the membrane. Figure 1 B) The internal inorganic particles are evenly dispersed, the pores are dense, there are very few holes, and the pore diameter is small, basically between 100-250nm, which can ensure the hydrophilicity and density of the diaphragm.
[0080] However, the reference sample 1# has a large number of holes, and the hole diameters are significantly larger, with many holes even reaching 400-750nm in diameter.
[0081] like Figure 4 As shown, the diaphragm prepared by the present method can still maintain a relatively good flatness (A) after being cross-folded, but the diaphragm prepared in comparative example 1 leaves an obvious crease (B) after being cross-folded, indicating that the present invention also solves the problem of poor bending resistance of existing diaphragms.
[0082] Embodiment 2:
[0083] (1) Coating solution preparation: zirconium hydroxide, polyethersulfone, methanol, NEP and dimethyl phthalate were mixed in a mass ratio of 50:20:5:50:5, and fully mixed at 80°C until completely dissolved and uniform. The mixed homogeneous solution was then vacuum degassed to obtain a casting solution.
[0084] (2) Coating: Heat the base film to 80°C, and use a comma scraper to evenly coat the casting liquid on both sides of the base film. The coating thickness on each side is controlled to be 300 μm.
[0085] (3) Phase inversion step 1: Place the coated membrane in an air medium at a temperature of 35° C. and a relative humidity of 90% RH for 300 seconds.
[0086] (4) Phase inversion step 2: Place the membrane in a -80°C liquid nitrogen environment for 5 minutes.
[0087] (5) Diaphragm molding: Place the diaphragm in a vacuum drying oven (vacuum degree <10 4 Pa), first dried at 50°C for 1 h, and then dried at 100°C for 1 h. The resulting diaphragm sample was marked as sample 2#.
[0088] Embodiment 3:
[0089] (1) Coating solution preparation: barium sulfate, polyphenylsulfone, ethanol, NBP and diethyl phthalate were mixed together in a mass ratio of 40:15:3:40:2, and fully mixed at 100°C until they were completely dissolved and uniform. Then, the mixed homogeneous solution was vacuum degassed to obtain a casting solution.
[0090] (2) Coating: Heat the base film to 70°C, and use a comma scraper to evenly coat the casting liquid on both sides of the base film. The coating thickness on each side is controlled to be 200 μm.
[0091] (3) Phase inversion step 1: Place the coated membrane in an air medium at a temperature of 25° C. and a relative humidity of 80% RH for 60 seconds.
[0092] (4) Phase inversion step 2: Place the membrane in a -60°C liquid nitrogen environment for 3 minutes.
[0093] (5) Diaphragm molding: Place the diaphragm in a vacuum drying oven (vacuum degree <10 4 Pa), first dried at 40°C for 2h, and then dried at 90°C for 2h. The obtained diaphragm sample was marked as sample 3#.
[0094] Reference Figure 2 The products obtained in Examples 2 and 3 have uniformly dispersed inorganic particles, dense pores, and very few pores, especially sample 3#, where the pore diameters are between 100-300 nm, which can ensure the hydrophilicity and density of the diaphragm.
[0095] Example 4
[0096] (1) Coating solution preparation: Magnesium oxide, polyimide, propanol, DMAC and dibutyl phthalate were mixed together in a mass ratio of 35:13:2:40:1, and fully mixed at 80° C. until they were completely dissolved and uniform. The mixed homogeneous solution was then vacuum degassed to obtain a casting solution.
[0097] (2) Coating: Heat the base film to 80°C, and use a comma scraper to evenly coat the casting liquid on both sides of the base film. The coating thickness is controlled at 250 um.
[0098] (3) Phase inversion step 1: Place the coated membrane in an air medium at a temperature of 25° C. and a relative humidity of 80% RH for 60 seconds.
[0099] (4) Phase inversion step 2: Place the membrane in a -60°C liquid nitrogen environment for 3 minutes.
[0100] (5) Diaphragm molding: Place the diaphragm in a vacuum drying oven (vacuum degree <10 4 Pa), first dried at 40°C for 2h, then dried at 90°C for 2h, and the obtained diaphragm sample was marked as sample 4#.
[0101] Example 5
[0102] (1) Coating solution preparation: zirconium oxide, polysulfone, glycerol, and NMP were mixed together in a mass ratio of 35:13:2:40, and fully mixed at 80° C. until they were completely dissolved and uniform. The mixed homogeneous solution was then vacuum degassed to obtain a casting solution.
[0103] (2) Coating: Heat the base film to 80°C, and use a comma scraper to evenly coat the casting liquid on both sides of the base film. The coating thickness on each side is controlled to be 250 μm.
[0104] (3) Phase inversion step 1: Place the coated membrane in an air medium at a temperature of 25° C. and a relative humidity of 80% RH for 60 seconds.
[0105] (4) Phase inversion step 2: Place the membrane in a -60°C liquid nitrogen environment for 3 minutes.
[0106] (5) Diaphragm molding: Place the diaphragm in a vacuum drying oven (vacuum degree <10 4 Pa), first dried at 40°C for 2h, then dried at 90°C for 2h, and the obtained diaphragm sample was marked as sample 5#.
[0107] Reference Figure 3 The products obtained in Examples 4 and 5 have uniformly dispersed inorganic particles, dense pores, and very few pores. Except for very few pores, the pore diameters are all between 100-300nm, which can ensure the hydrophilicity and density of the diaphragm. The number of pores in sample 4# is particularly small, while the pore diameter of sample 5# is very uniform.
[0108] The physical property parameter data of the samples prepared in the above five embodiments are shown in Table 1.
[0109] Table 1. Physical properties of composite membranes
[0110] Performance Indicators unit Sample 1# Sample 2# Sample 3# Sample 4# Sample 5# Total thickness μm 221 614 419 512 521 Porosity % 52 58 54 55 53 Sheet resistance <![CDATA[Ω / cm 2 ]]> 0.06 0.18 0.12 0.12 0.14 Bubble point pressure bar 2.1 3.9 2.6 3.2 3.3
[0111] like Figure 1-3 As shown in Table 1, compared with the diaphragm produced by the conventional method (reference sample 1#, the secondary phase inversion medium is 50°C water bath, oven drying), the diaphragm prepared by the present method (sample 1#, the secondary phase inversion medium is -60°C liquid nitrogen, vacuum two-step drying) has better uniformity, and almost no obvious pores are observed, and the average pore size is between 150-200nm.
[0112] The electrochemical test used a 4cm*4cm small water electrolysis hydrogen production electrolyzer, with commercial nickel mesh as the cathode and anode, 6M potassium hydroxide aqueous solution as the electrolyte, and the electrolyte temperature was 90℃. 2 ) is shown in Table 2 below.
[0113] Table 2, electrical properties of composite diaphragms
[0114] Current density Sample 1# Sample 2# Sample 3# Sample 4# Sample 5# Reference sample 1# <![CDATA[0.4A / cm 2 ]]> 1.62 1.68 1.68 1.64 1.73 1.79 <![CDATA[0.8A / cm 2 ]]> 1.70 1.76 1.77 1.72 1.82 1.88 <![CDATA[1.2A / cm 2 ]]> 1.93 1.98 1.97 1.96 2.02 2.05
[0115] It should be noted that the above contents are further detailed descriptions of the present invention in combination with specific implementation methods, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions; the dimensional data of this embodiment does not necessarily limit the technical solution, but only shows one of the specific working conditions. For ordinary technicians in the technical field to which the present invention belongs, several simple improvements and modifications can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.
Claims
1. A method for preparing a composite diaphragm for producing hydrogen by alkaline water electrolysis, characterized in that: The method comprises the following steps: uniformly mixing inorganic powder, resin and solvent to obtain a casting solution; coating the casting solution on both sides of the base film; The coated membrane is subjected to a phase inversion; Performing a second phase transformation on the membrane that has undergone a first phase transformation; The diaphragm that has undergone the secondary phase conversion is dried to obtain the alkaline water electrolysis hydrogen production composite diaphragm.
2. The method for preparing a composite diaphragm for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: The amounts of the inorganic powder, resin and solvent are calculated by mass: 30-50 parts by weight of inorganic powder, 8-25 parts by weight of resin, and 25-50 parts by weight of solvent.
3. The method for preparing a composite diaphragm for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: During the first phase inversion process, the temperature is 10-35°C, the relative humidity is 50-90%RH, and the residence time is 10-300s.
4. The method for preparing a composite diaphragm for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: The second phase inversion temperature is -30°C to -100°C, and the residence time is 1-15 min.
5. The method for preparing a composite diaphragm for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: The inorganic powder is selected from one or a combination of two or more of zirconium oxide, zirconium hydroxide, barium sulfate or magnesium oxide, the particle size D50 of the inorganic powder is less than 5 μm, and the maximum particle size of the inorganic powder does not exceed 10 μm; and / or The resin includes one or a combination of two or more of polysulfone, polyethersulfone, polyphenylsulfone, polyimide or sulfonated polyphenylene sulfide.
6. The method for preparing a composite diaphragm for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: During the preparation of the casting solution, a plasticizer and / or a poor solvent are also added; the amounts of the plasticizer and / or the poor solvent are calculated by mass as follows: 1-5 parts by weight of plasticizer, and / or 1-5 parts by weight of poor solvent.
7. The method for preparing a composite diaphragm for producing hydrogen by alkaline water electrolysis according to claim 6, characterized in that: The poor solvent is alcohol; and / or The plasticizer is selected from one or a combination of two or more of dimethyl phthalate, diethyl phthalate or dibutyl phthalate.
8. The method for preparing a composite diaphragm for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: The preparation temperature of the casting solution is 60-100° C.; the temperature of the base film is maintained at 60-85° C. before coating, and the coating thickness of the casting solution on each side of the base film is independently 100-350 μm.
9. The method for preparing a composite diaphragm for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: The drying conditions of the diaphragm are as follows: vacuum drying at 30-60° C. for 1-4 h in the first step; and vacuum drying at 70-100° C. for 1-4 h in the second step.
10. A composite membrane for producing hydrogen by alkaline water electrolysis prepared by the method of claim 1, characterized in that: The alkaline water electrolysis hydrogen production composite diaphragm consists of a base membrane and casting liquid coatings on both sides thereof, and the porosity of the casting liquid coating is 40-80%.
Citation Information
Patent Citations
Diaphragm for alkaline water electrolysis
CN115997046A
Composite diaphragm for hydrogen production by alkaline electrolyzed water, and preparation method for composite diaphragm
WO2024140892A1
Cited By
Method for reducing extraction residual agent of wet-process diaphragm base membrane
CN120960827A